Cell wall-bound coniferyl Alcohol oxidase associated with lignification in coniofers - Savidge, Rodney A.; Randeniya, Preethi Udagama (Phytochemistry, 1992)
An enzyme utilizing O2 to oxidize coniferyl alcohol into a lignin-like product is described. This enzyme has been found firmly bound to cell walls in developing xylem of Pinus strobus, Abies balsamea, Larix laricina, Picea rubens and Pinus banksiana. In each of these conifers, oxidase activity arises in synchrony with initiation of lignification and disappears with termination of lignification. By combined gas chromatography-mass spectrometry, the enzyme was found to oxidize coniferyl alcohol into dehydrodiconiferyl alcohol and pinoresinol, and by UV microscopy it was determined that under aerobic in vitro conditions the enzyme converts coniferyl alcohol into hydrophobic globules similar to guaiacyl lignin. By isoelectric focusing, several oxidase isoenzymes were resolved; all appear to be glycoproteins.
Keywords: Pinus; Abies; Larix; Picea; Gymnospermae; cambial growth; enzymes; glycoprotein; leaves; lignin; secondary wall development; tracheid differentiation; wood formation